Technology, violence, and war
1 online resource.
Keywords: This volume explores the importance of technology in war, and to the study of warfare. Dr. Guilmartin's former students explore how technology from the medieval to the modern era, and across several continents, was integral to warfare and to the outcomes of wars. Authors discuss the interactions between politics, grand strategy, war, technology, and the socio-cultural implementation of new technologies in different contexts. They explore how and why belligerents chose to employ new technologies, the intended and unintended consequences of doing so, the feedback loops driving these consequences, and how the warring powers came to grips with the new technologies they unleashed. This work is particularly useful for military historians, military professionals, and policymakers who study and face analogous situations. Contributors are Alan Beyerchen, Robert H. Clemm, Edward Coss, Sebastian Cox, Daniel P. M. Curzon, Sarah K. Douglas, Robert S. Ehlers, Jr., Andrew de la Garza, John F. Guilmartin, Jr., Matthew Hurley, Peter Mansoor, Edward B. McCaul, Jr., Michael Pavelec, William Roberts, Robyn Rodriguez, Clifford J. Rogers, William Waddell, and Corbin Williamson.